2015
DOI: 10.5539/ijel.v5n5p75
|View full text |Cite
|
Sign up to set email alerts
|

A Survey of English Phonetics Instruction in China

Abstract: Although pronunciation is a salient component of effective oral communication, English phonetics instruction has long been marginalized in China and relevant research is also scarce. To bridge this gap, we did a survey of 64 English majors from a Chinese university and 13 English Phonetics quality courses on national, provincial and collegiate levels constructed from 2004 to 2014 by Chinese universities. Our survey study disclosed tertiary-level students' perceptions of English phonetics instruction and the st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Besides, both previous studies are Lintunen and Mäkilähde (2015), and Pei and Qin (2015) mentioned that learners tend to be unconfident in pronouncing English words. On the contrary, more than half of students tend to be more confident with it (statement 12).…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Besides, both previous studies are Lintunen and Mäkilähde (2015), and Pei and Qin (2015) mentioned that learners tend to be unconfident in pronouncing English words. On the contrary, more than half of students tend to be more confident with it (statement 12).…”
Section: Discussionmentioning
confidence: 91%
“…One of the less is conducted by involving 103 Indonesian EFL learners reported that they performed a positive attitude toward English phonetics teaching yet did not think that they need it for their future life. Additionally, research done by Pei and Qin (2015) reported that 70% of 64 participants thought that English phonetics is important and significant to help them pronounce better. The aforementioned discussion has implied that the study of English learners toward English phonetics is mostly positives, yet, less exploration on Indonesian EFL learners and English phonetics learning in Indonesia.…”
Section: Introductionmentioning
confidence: 99%
“…IPA teaching only has pronunciation methods, but the intonation depends on the individual teacher, so it will cause the accent problem of multiple intonations of a word. Chinese education experts say that English phonetics teaching has been marginalized in Chinese English classes, which has also led to pronunciation becoming a major obstacle for Chinese people to talk with foreigners [6]. It is difficult to correct in the future after being influenced by the wrong accent at the beginner stage.…”
Section: Introduction Of the International Phonetic Alphabet And Its ...mentioning
confidence: 99%
“…Unfortunately, it appears that more attention is still paid to grammar and lexis despite the fact that pronunciation instruction is also a really essential part of teaching English systems (Pei & Qin, 2015;Gilakjani & Sabouri, 2016). Furthermore, motivation as one of the prerequisites for a successful educational process and opportunities for pronunciation practice are also vitally important (Bírová Ocovay, & Vasbieva, 2016).…”
Section: Teaching [θ] and [ð] To Efl Learnersmentioning
confidence: 99%